2020
DOI: 10.1111/1462-2920.15016
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to arsenic contaminant among multidrug‐resistant and copper‐tolerant Salmonella successful clones is associated with diverse ars operons and genetic contexts

Abstract: Summary Emergence and expansion of frequent multidrug‐resistant (MDR) major Salmonella clones/serotypes has been a significant threat in the last years. Metal compounds, such as copper, commonly used in animal‐production settings, have been pointed out as possible contributors for the selection of such strains/clones. However, the scarcity of studies limits our understanding of the impact of other metal environmental contaminants as arsenic (used in insecticides/herbicides/coccidiostats). We analysed arsenic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 65 publications
(110 reference statements)
0
20
0
Order By: Relevance
“…Other investigators have also suggested that the acquisition of metal tolerance genes is attributed to the use of metals (e.g., zinc and copper) as antimicrobial agents in human healthcare or in agriculture, and this practice has potentially contributed to the emergence of clinically relevant Salmonella isolates by aiding their survival in metal-contaminated settings, such as swine production [60,61]. Mourao et al suggested that acquisition of the arsenic resistance gene arsBII by Salmonella I 4, [5],12:i:has resulted in a foodborne pathogen resistant to arsenic compounds used in insecticides, herbicides, and coccidiostats [62]. Furthermore, a comparative whole-genome analysis of 50 epidemiologically unrelated serovar I 4, [5],12:i:-isolates from Italy revealed the widespread presence of heavy metal tolerance gene cassettes, with most of the Salmonella strains containing copper and silver resistance genes and half of the isolates also containing the mercury tolerance gene merA [7].…”
Section: Copper Induced Gene Expression Of Metal Tolerance Genes On Genomic Islandsmentioning
confidence: 99%
“…Other investigators have also suggested that the acquisition of metal tolerance genes is attributed to the use of metals (e.g., zinc and copper) as antimicrobial agents in human healthcare or in agriculture, and this practice has potentially contributed to the emergence of clinically relevant Salmonella isolates by aiding their survival in metal-contaminated settings, such as swine production [60,61]. Mourao et al suggested that acquisition of the arsenic resistance gene arsBII by Salmonella I 4, [5],12:i:has resulted in a foodborne pathogen resistant to arsenic compounds used in insecticides, herbicides, and coccidiostats [62]. Furthermore, a comparative whole-genome analysis of 50 epidemiologically unrelated serovar I 4, [5],12:i:-isolates from Italy revealed the widespread presence of heavy metal tolerance gene cassettes, with most of the Salmonella strains containing copper and silver resistance genes and half of the isolates also containing the mercury tolerance gene merA [7].…”
Section: Copper Induced Gene Expression Of Metal Tolerance Genes On Genomic Islandsmentioning
confidence: 99%
“…This island has previously been shown to increase the ability of a bacterium to survive in an environment with higher levels of copper and silver, as well as the ability to provide tolerance during the transition between aerobic and anaerobic environments, affording a fitness advantage for facultative anaerobes (43, 45). The use of copper as a growth promoter in swine and poultry has led to the selection of this island in Salmonella associated with these sources in other countries (46, 47). The use of copper as a fungicide and bactericide in agriculture has been reported for many years, and it is generally considered safe for both conventional and organic produce use (48, 49).…”
Section: Resultsmentioning
confidence: 99%
“…The S . 1,4,[5],12:i:- poultry isolates presented the typical antibiotic resistance ( bla TEM + strA-strB + sul2 ± tetB ) and metal tolerance ( pcoD + silA + arsB ± merA ) features of the widespread clinically relevant European clone (ST34) [ 16 , 17 ]. Resistance to the tested antibiotics and tolerance to copper (MICs = 32 mM) was restricted to S .…”
Section: Resultsmentioning
confidence: 99%
“…1,4,[5],12:i:- copper tolerant strains might also have the ability to escape the metal-mediated antimicrobial response of human macrophages [ 70 ]. In the context of antibiotic reducing/replacing, the extensive use of heavy metals for animal growth promotion (copper and zinc) as well as mercury and arsenic compounds accumulation in the agriculture environment [ 17 ], might be potential factors contributing to the persistence and expansion of this emerging S . 1,4,[5],12:i:- ST3478 clonal lineage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation